The Impact of ESG Regulation on Financial Stability : A Comparative Analysis of Europe and Latin America - Mejia, Daniela; Jílková, Petra; Fiala, Lukáš; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2025)
This thesis investigates the impact of Environmental, Social, and Governance (ESG) performance on the financial stability and profitability of banks in the European Union (EU) and Latin America (LATAM). This study employs panel data regression analysis for 20 leading commercial banks, 10 per region, over the period 2013–2023, to evaluate whether higher ESG scores are associated with more favorable financial stability and profitability indicators. Specifically, Z-scores, lower non-performing loan (NPL) ratios, stronger capital adequacy (CAR), enhanced liquidity as measured by the current ratio, and profitability (ROA). The results indicate that ESG performance has a statistically significant and favorable relationship when it comes to credit quality in EU banks, as shown by lower NPL ratios across all ESG dimensions. However, no robust evidence is found when it comes to ESG scores and overall financial stability (Z-score) or profitability (ROA) in either region. A trade-off is observed between ESG scores and short-term liquidity (current ratio) in both regions, likely reflecting strategical capital allocation on behalf of these banks. The findings support the hypothesis that ESG influences financial stability more significantly in the EU rather than in LATAM. The results highlight the importance of regulatory maturity and institutional pressures in influencing financial stability. This research contributes to the topic of ESG reporting, by offering insight into the relationship between ESG performance and financial stability.
Vedoucí práce: Petra Jílková
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: finance and accounting [obor dipl. práce]; diplomové práce; master's theses